2011
DOI: 10.1136/hrt.2010.205880
|View full text |Cite
|
Sign up to set email alerts
|

Plakophilin 2A is the dominant isoform in human heart tissue: consequences for the genetic screening of arrhythmogenic right ventricular cardiomyopathy

Abstract: PKP2A was shown to be the major isoform expressed in human heart tissue and PKP2B protein was undetectable. The results strongly suggest that p.Arg490Trp and other variants located in PKP2 exon 6 may not be disease causing. Variant splicing also has important consequences for the interpretation of mutation analysis and genetic counselling in ARVC and other hereditary cardiac diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Recently, Gandjbakhch et al found PKP2a was shown to be the major isoform expressed in human heart tissue and PKP2b protein was undetectable. 30 PKP 2 interacts with desmoplakin, plakoglobin, Dsg 1 and 2, and Dsc 1a and 2a, with the head domain apparently being critical for the assembly and maintenance of desmosomes. 31 In addition, PKP 2 is capable of associating with β-catenin, thereby regulating its signaling activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gandjbakhch et al found PKP2a was shown to be the major isoform expressed in human heart tissue and PKP2b protein was undetectable. 30 PKP 2 interacts with desmoplakin, plakoglobin, Dsg 1 and 2, and Dsc 1a and 2a, with the head domain apparently being critical for the assembly and maintenance of desmosomes. 31 In addition, PKP 2 is capable of associating with β-catenin, thereby regulating its signaling activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a genetic database needs to be constantly revised and updated as new genes, variants, and papers appear, and the pathogenicity of variants is revised. It has been suggested, for instance, that the missense variant p.R490W in PKP2 may not be a causative mutation as it is located in exon 6, which is skipped in the cardiac isoform PKP2a [Gandjbakhch et al., ]. In another example, the p.A897KfsX4 frameshift variation in DSC2 was reclassified from pathogenic to a single‐nucleotide polymorphism after it was identified in 1.5% of control subjects [De Bortoli et al., ].…”
Section: Introductionmentioning
confidence: 99%
“…As the two major isoforms of Pkp2 (Table 1) based on alternative splicing of the primary gene products and termed Pkp2a and Pkp2b (Christensen et al 2010b; Gandjbakhch et al 2011; Mertens et al 1996, 1999; Schmidt and Jaeger 2005; Watkins et al 2009) might differ in their local detectability with immunocytochemical methods and might be located in different positions, I generated antibodies (Abs) of high specificity and affinity allowing reliable Pkp2-reactions on sections through formaldehyde-fixed, paraffin-embedded tissue samples as well as on cultured cells (see also Schmidt et al 1997). The monoclonal and polyclonal Abs selected gave essentially similar results with immunoblotting of SDS-PAGE-separated polypeptides of normal and tumor tissue samples, including vertebrate heart tissue and cell cultures (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…For two of the Pkps, two prominent splice variants of the gene products have been determined (Hatzfeld et al 1994; Heid et al 1994; Mertens et al 1996; Schmidt et al 1994; see also Gandjbakhch et al 2011). Finally and rather surprisingly, diffusible nuclear and cytoplasmic forms, including some rather stable functional complexes, have also been described for all three Pkps (e.g., Bass-Zubek et al 2008; Bonné et al 1999; Hofmann et al 2006; Mertens et al 1996, 2001; Mueller et al 2003; Schmidt et al 1997).…”
Section: Introductionmentioning
confidence: 99%